Analisis Tingkat Asupan Makronutrien dan Berat Badan Prajurit Kavaleri TNI AD Selama Diet Penurunan Berat Badan di Bandung dan Jakarta - Shafa Almira Septianingrum; Emyr Reisha Isaura (Media Gizi Kesmas, 2023)
Background: TNI AD has role as national defense to protect the state from military theats. The duties of TNI AD are to maintain state sovereignty, territorial integrity, and state security. Excellent physical condition is needed to perform their duties that prioritize vigorous physical activity. Every six months, TNI AD conduct physical test to assess their fitness and strenght. Soldier who has low score on physical test are recommended to take physical training and adjust their diet Objectives: The purposes of this study is to analyze macronutrients intake and body weight alteration on the Kavaleri TNI AD soldiers with weight loss diet in Bandung and Jakarta. Methods: This research was a case-control study and was conducted online using google form that was distributed through commanders in the Yonkav 4/KC Bandung, Yonkav 7/PS Jakarta, and Denkavkud Bandung. The number of samples are 43 respondents with purposive sampling. Research instruments were SQ-FFQ to measure macronutrient intake in one month and IPAQ-SF to determine the physical activity level. The results of macronutrient intake were compared with AKG 2019 and their nutritional requirement. Results: the results showed that majority of respondents had deficit macronutrients intake. The median of energy fulfillment is 50.44% of energy requirement. From this intake level, there is significant reduction in body weight (p<0.001) with median difference is 2 kg. Conclusion: The diet tended to be in calorie deficit and could lose weight significantly (p<0.001). nutritionist assistance is needed to give diet recommendation.